2015
DOI: 10.1016/j.proeps.2015.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Assessment on the Characteristics and the Damping Performance of Coastal Forests in Pangandaran after the 2006 Java Tsunami

Abstract: The use of coastal forests as natural tsunami barrier has long been the source of controversies due to inconclusive understanding on the damping performance and contradictory field findings from the last tsunami events. After experiencing hundreds of casualties and severe destruction on the infrastructures due to the 2006 South Java Tsunami, the coastline of Pangandaran district in West Java was replanted by coastal forest vegetation to mitigate future tsunami as well as improving the quality of the environmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 10 publications
0
10
0
4
Order By: Relevance
“…Based on research [14][15][16][17]. the speed of the tsunami depends on the depth of the waters, as a result, the waves accelerate or slow down following the increase or decrease in the depth of the waters, with this process the direction of movement of the waves also changes and the bias wave energy becomes focused or also spreads.…”
Section: Table-i: Values and Areas Of Tsunami Hazard Levelsmentioning
confidence: 99%
“…Based on research [14][15][16][17]. the speed of the tsunami depends on the depth of the waters, as a result, the waves accelerate or slow down following the increase or decrease in the depth of the waters, with this process the direction of movement of the waves also changes and the bias wave energy becomes focused or also spreads.…”
Section: Table-i: Values and Areas Of Tsunami Hazard Levelsmentioning
confidence: 99%
“…Hence, Licensed Under Creative Commons Attribution CC BY those five villages have the availability of freshwater at a distance less than 500 meters from the shoreline, 0.2 kilometers precisely. Seabed materials in Pangandaran is the sand, of which size ranks from fine to very fine, including those that are part of the sand dunes [11].…”
Section: Coastal Tourism Suitabilitymentioning
confidence: 99%
“…Several assessments have been made of the future tsunami risk potential in Pangandaran (Bisri 2011;Faiqoh et al 2013;Husrin et al 2015;Mardiatno et al 2020;Windupranata et al 2020). Bisri (2011) found that the areas of local governance, disaster recovery, and the emergency response were weak.…”
Section: Introductionmentioning
confidence: 99%